Reaching the Homeless Patient Population: A Novel Student-Run Clinic Outreach Program - Lichter, Bailee; Paulsen, Riley T.; Buchholz, Alaire; Buchanan, Jamuna; Quinn, Garrett; van Oosbree, Annika (Journal of Student-Run Clinics, 2025)
Introduction: The Bishop Dudley Hospitality House (BDHH) is a non-profit organization founded in 2015 that provides support services, resources, and shelter to the poor and homeless community members of Sioux Falls, South Dakota. Recognizing that physical access to healthcare is a major barrier for many individuals that utilize the BDHH, University of South Dakota Sanford School of Medicine student leaders at the Coyote Clinic instituted a bimonthly satellite clinic in the on-site BDHH clinic room. Methods: In this study, we first describe the establishment of the collaboration between a student-run free clinic and a community homeless shelter. Additionally, to demonstrate the impact of such an outreach and subsequent referral program, we have collected and analyzed data regarding the demographics, insurance status, and access to a primary care provider of the patients, their chief complaints, acuity level, referrals, and whether they attended their follow-up appointment. Results: Over the course of February 1, 2022 through June 30, 2023, a total of 80 clinical encounters and 57 patients were seen at the Coyote Clinic BDHH Satellite Clinic. A total of 29 referrals to the main Coyote Clinic downtown were made and one patient was sent to the Emergency Department directly from BDHH. Conclusions: The BDHH satellite clinic has created an additional entry point for healthcare to a high-risk population. Our hope is this model can be adopted by other student-run free clinics seeking to serve similar patient populations.